Measures to ensuring digital transformation and inclusive economic growth of regions - Zokirova Bakhora Zakir kizi (THE INNOVATION ECONOMY, 2026)
This article explores the role and significance of digital transformation in ensuring inclusive economic growth at the regional level. Special attention is given to the use of digital technologies to reduce economic disparities, create job opportunities, and expand economic prospects in underdeveloped regions. The paper examines key principles of digital transformation that contribute to socio-economic progress and inclusive development.